Melding caged compounds with supramolecular containers: photogeneration and miscreant behavior of the coumarylmethyl carbocation - Kamatham, Nareshbabu (2019)
By merging well-established concepts of supramolecular chemistry, protecting group strategy, and photochemistry, we have solubilized in water hydrophobic organic molecules consisting of a photoactive protecting group and masked carboxylic acids, released the desired acid, and confined a reactive carbocation intermediate within a capsule. Confinement of the photogenerated carbo cation brought out the latent radical-like behavior. This observation is consistent with the recent theoretical prediction of the 7-(diethylamino)coumarinyl-4-methyl carbocation having a triplet diradical ground-state electronic contribution.